POLIGAMI: KESAKRALAN DI ANTARA PERSIMPANGAN TEKSTUAL DAN KONTEKSTUAL - Handayani, Tri (STIQ Al-Lathifiyyah Palembang, 2019)
The authenticity of the Qur'an as a scripture is undoubted by its adherents. But when they talk and deal with polygamy verse, it seems it was rejected. Ziauddin Sardar stated that this polygamous verse denotes prohibition. In line with Sardar, Siti Musdah Mulia thinks that polygamy degrades the dignity and value of women. The view of both figures areat odds with texts in well-documented hadith literature that lead to its allowance. This paper attempts to understand both pro and contra sides by accommodating some of the insights and approaches that make it possible to understand this verse.